Pathophysiological Bases of Comorbidity in Migraine - Altamura, Claudia; Corbelli, Ilenia; de Tommaso, Marina; Di Lorenzo, Cherubino; Di Lorenzo, Giorgio; Di Renzo, Antonio; Filippi, Massimo; Jannini, Tommaso B.; Messina, Roberta; Parisi, Pasquale; Parisi, Vincenzo; Pierelli, Francesco; et al. (Frontiers in Human Neuroscience, 2021)
Despite it is commonly accepted that migraine is a disorder of the nervous system with a prominent genetic basis, it is comorbid with a plethora of medical conditions. Several studies have found bidirectional comorbidity between migraine and different disorders including neurological, psychiatric, cardio- and cerebrovascular, gastrointestinal, metaboloendocrine, and immunological conditions. Each of these has its own genetic load and shares some common characteristics with migraine. The bi-directional mechanisms that are likely to underlie this extensive comorbidity between migraine and other diseases are manifold. Comorbid pathologies can induce and promote thalamocortical network dysexcitability, multi-organ transient or persistent pro-inflammatory state, and disproportionate energetic needs in a variable combination, which in turn may be causative mechanisms of the activation of an ample defensive system with includes the trigeminovascular system in conjunction with the neuroendocrine hypothalamic system. This strategy is designed to maintain brain homeostasis by regulating homeostatic needs, such as normal subcortico-cortical excitability, energy balance, osmoregulation, and emotional response. In this light, the treatment of migraine should always involve a multidisciplinary approach, aimed at identifying and, if necessary, eliminating possible risk and comorbidity factors.